Current surgical rehabilitation techniques for patients with total bilateral symblepharon - S.A. Iakimenko; P.O. Kostenko (Ukrainian Society of Ophthalmologists, 2019)
Purpose: To investigate the efficacy of a three-stage surgical rehabilitation technique for patients with bilateral total symblepharon; the technique has been developed and advanced and is being used at present at the Ocular Burn Injury Department. Materials and Methods: We investigated the outcomes of patients with bilateral total symblepharon undergoing either of the two oral mucosal autotransplantation procedures developed for symblepharon removal at the department. A total of 86 patients with bilateral total symblepharon underwent either of the two procedures during 2005 to 2018. Of these patients, 34 (39.5%) had the two-stage procedure, and 52 (60.5%), the three-stage procedure. Results: Constructed fornices were assessed with objective measurements of forniceal depth and symmetry, and presence or absence of entropion. Our three-stage technique allowed us to transplant more labial mucosal grafts during the first two stages, with a success rate of 86.5% (46 patients), compared to 76.5% (26 patients) for the two-stage technique. In addition, of the patients who had the three-stage surgical rehabilitation procedure, only 17.3% (9 patients) developed transitory intraocular hypertension, compared to 23.5% (8 patients) for those who had the two-stage procedure. Conclusion: The three-stage surgical rehabilitation technique for patients with total bilateral symblepharon was developed and piloted at the Ocular Burn Injury Department, and was found safe and effective. This allows recommending it for widespread use in ophthalmological practice.